Comparison of spray-dried blood meal and fish by-products in the phase II starter pig diet - L J Kats; J L Laurin; Michael D Tokach; Jim L Nelssen; Robert D Goodband (Kansas Agricultural Experiment Station Research Reports, 1992)
A total of 311 weanling pigs (initially 10.9 lb and 17 d of age) was used to compare fish by-products, spray-dried blood meal and combinations of spray-dried blood meal and fish by-products in the phase II (d 7 to 25) diet. Pigs were allotted by weight to one of five experimental treatments with 8 to 11 pigs/pen and seven replications. Pigs were placed on a common phase I diet (d 0 to 7 postweaning) that contained 7.5%spray-dried porcine plasma, 1.75% spray-dried blood meal, and 20% dried whey. The phase I diet was formulated to contain 1.5% lysine, .9% Ca, and .8% P. Pigs were then randomly assigned to one of five dietary treatments. All phase II diets (d 7 to 25 postweaning) contained 10% dried whey and were formulated to contain 1.25% lysine and .36% methionine. The control diet contained 2.5% spray-dried blood meal (SDBM) and 10% dried whey. Select menhaden fish meal (SMFM) and spray-dried fish hydrolysate (SDFH) replaced SDBM on an equal lysine basis at 5% and 4.8%, respectively, and 2.5% SMFM + 1.25% SDBM and 2.0% SDFH + 1.25% SDBM were used in combinations to form the other four dietary treatments. Average daily gain (ADG), average daily feed intake (ADFI), and feed efficiency (F/G) were improved with the addition of SDBM in the fIrst week (d 7 to 14) of phase II. No differences were observed in ADG and ADFI for the overall phase II period. Pigs fed SDBM had poorer FIG (d 7 to 25) compared to pigs fed either SMFM or SDFH. However, SDBM was the most cost effective protein source in this experiment.; Swine Day, Manhattan, KS, November 19, 1992
Keywords: Swine day; 1992; Kansas Agricultural Experiment Station contribution; no. 93-142-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 667; Swine; Starter pig; Fish by-products; Blood Meal